Bimbingan Teknis Kepenulisan Karya Ilmiah Untuk Meningkatkan Keterampilan Menulis Proposal Mahasiswa Universitas Nahdlatul Ulama Blitar - Saptono Hadi; Enggal Chairyadi (Jurnal Pengabdian Masyarakat Bestari, 2022)
In an effort to enhance human resources, particularly intellectual and personality talents in developing scientific writing skills and enhancing thinking skills, this community service program engages the college community (soft skills and hard skills). The targets are especially the 3rd-semester students of PIAUDI and students of Universitas Nahdlatul Ulama Blitar, held in September December 2020. This cooperative learning is able to bring companins  who are more creative, innovative, and competitive to overcome actual, real problems in an effort to solve them. It does this through the use of lectures, discussions, STAD (Student Teams Achievement Division), and Problem Based Learning (PBL) models. Results showed that overall service implementation went well and generated a lot of optimism, increasing accomplishment from an initial understanding of 40% (12 participants) who knew little about scientific writing to an increase of 83.3 percent (25 children) who could make scientific proposals, participants wanted more coaching.